PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP KELENGKAPAN PENGUNGKAPAN PADA LAPORAN KEUANGAN TAHUNAN PERUSAHAAN PROPERTI DAN REAL ESTATE - Heniwati, Elok; Yani, Erma (Fakultas Ekonomi dan Bisnis, UNTAN, 2011)
The objective of this study is to examine the influence of firm size, debt to equity ratio, board of commissioner size, and return on equity to full disclosure of annual report. This study takes sample from 23 companies in the property and real estate sector listing at the Indonesian Stock Exchange, which were published in financial report from 2007-2010. This research uses multiple regression analysis as research analysis.The results of this study show that simultantly there is a significant influence between firm charasterictics and full disclosure of annual report. Partially, firm size has positive sign to full disclosure of annual report. Meanwhile, debt to equity ratio, board of commissioner size and return on equity has negative sign to full disclosure of annual report. It means that firm size influences to full disclosure of annual report. Otherwise, debt to equity ratio, board of commissioner size and return on equity has no influence to full disclosure of annual report.